Early gastric cancer successfully treated by endoscopic submucosal resection 1 year after laparoscopic sleeve gastrectomy with duodenal‐jejunal bypass. Issue 3 (17th July 2018) - Seki, Yosuke; Kasama, Kazunori; Tanaka, Tatsuro; Baba, Satoshi; Ito, Masayoshi; Kurokawa, Yoshimochi
Abstract: This case involved a 64‐year‐old female patient with a BMI of 35.3 kg/m 2 and poorly controlled type 2 diabetes mellitus. Preoperative upper gastrointestinal endoscopy revealed chronic, atrophic gastritis. Helicobacter pylori antibody was negative. The patient underwent laparoscopic sleeve gastrectomy with duodenal‐jejunal bypass as a metabolic surgery to treat obesity and type 2 diabetes mellitus. At 1 year postoperatively, routine endoscopy detected a flat elevated lesion at the distal gastric sleeve, near the posterior wall of the antrum; biopsy revealed adenocarcinoma. Endoscopic submucosal resection was performed without complication. This case shows the advantage of laparoscopic sleeve gastrectomy with duodenal‐jejunal bypass in screening the excluded stomach as compared to laparoscopic Roux‐en‐Y gastric bypass. Therefore, laparoscopic sleeve gastrectomy with duodenal‐jejunal bypass can be a viable alternative to laparoscopic Roux‐en‐Y gastric bypass for regions where gastric cancer is endemic.